2008
DOI: 10.1029/2008gl035627
|View full text |Cite
|
Sign up to set email alerts
|

Wind speed climatology and trends for Australia, 1975–2006: Capturing the stilling phenomenon and comparison with near‐surface reanalysis output

Abstract: 1] Near-surface wind speeds (u) measured by terrestrial anemometers show declines (a 'stilling') at a range of midlatitude sites, but two gridded u datasets (a NCEP/NCAR reanalysis output and a surface-pressure-based u model) have not reproduced the stilling observed at Australian stations. We developed Australia-wide 0.01°resolution daily u grids by interpolating measurements from an expanded anemometer network for 1975 -2006. These new grids represented the magnitude and spatialvariability of observed u tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
264
6
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 369 publications
(302 citation statements)
references
References 39 publications
29
264
6
3
Order By: Relevance
“…As for changes in W , many parts of the world reported to have experienced a deceleration pattern in W such as the one that had occurred in the TRSR during the last 30 to 50 years. For example, please see You et al (2010b), Ren et al (2005aRen et al ( , 2005b, Xu et al (2006), Ko et al (2010), Hobbins (2004), Tuller (2004), and McVicar et al (2008.…”
Section: Temporal Characteristics Of Trsr Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…As for changes in W , many parts of the world reported to have experienced a deceleration pattern in W such as the one that had occurred in the TRSR during the last 30 to 50 years. For example, please see You et al (2010b), Ren et al (2005aRen et al ( , 2005b, Xu et al (2006), Ko et al (2010), Hobbins (2004), Tuller (2004), and McVicar et al (2008.…”
Section: Temporal Characteristics Of Trsr Climate Changementioning
confidence: 99%
“…Climate change is virtually irreversible, a manifestation of multiple factors (da Silva, 2004), such as rising temperatures (Ding et al, 2006;IPCC, 2007) as well as changes in precipitation , reference crop evapotranspiration (Liang et al, 2010), wind speed (McVicar et al, 2008), drought events (Potop et al, 2008), and solar radiation (Wild, 2009) to name a few examples. Observations have unearthed climate change impacts on environments and natural resources.…”
Section: Introductionmentioning
confidence: 99%
“…For example, wind speed changes may impact the viability of wind energy operations (Pryor et al, 2006), wave climates and storm surges (Debernard and Roed, 2008) and hence shipping, marine and offshore industries (Knippertz et al, 2000;Pirazzoli and Tomasin, 2003). Changes in wind speed may affect soil moisture, evaporation and water resources (McVicar et al, 2008;Zhang et al, 2007), which may influence the evolution of arid and semi-arid environments (Okin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A decline of near-surface wind speed in recent years has been observed in China, the Czech Republic, the United States, and Australia (McVicar et al, 2008;Brázdil et al, 2009;Pryor et al, 2009;Yang et al, 2012). It has been reported that wind speed declined by 5%-15% in the midlatitudes of the NH between 1979 and 2008 (Vautard et al, 2010).…”
Section: Relationship Between Global Frictional Torque and Mean Zonalmentioning
confidence: 99%